½-homogeneous hyperspaces - Macias, Sergio (Topology Proceedings, 2021)
Sam B. Nadler, Jr. and Patricia Pellicer-Covarrubias studied the 12-homogeneity of the hyperspace of subcontinua of a continuum X. We continue this investigation and include results about the 12-homogeneity of the hyperspace suspension of X.